2017
DOI: 10.1007/s00431-017-2933-9
|View full text |Cite
|
Sign up to set email alerts
|

Premedication with melatonin vs midazolam: efficacy on anxiety and compliance in paediatric surgical patients

Abstract: This study adds new encouraging data, further supporting the potential use of melatonin premedication in reducing anxiety and improving compliance to induction of anaesthesia in children undergoing surgery. Nevertheless, further larger controlled clinical trials are needed to confirm the real effectiveness of melatonin as a premedicant agent in paediatric population. What is Known: • Although midazolam represents the preferred treatment as a premedication for children before induction of anaesthesia, it has se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 40 publications
0
44
0
1
Order By: Relevance
“…was as effective as midazolam in reducing pre-operative anxiety. [ 54 , 55 ] With higher doses (0.75 mg/kg), melatonin was found to be more effective than midazolam for pre-operative anxiety without causing sedation and cognitive dysfunctions as midazolam did. [ 55 ] Patel et al (2015) found similar results with adults, whereas Caumo et al (2009) showed that melatonin was as effective as clonidine in reducing post-operative anxiety.…”
Section: Anxiety In Asdmentioning
confidence: 99%
“…was as effective as midazolam in reducing pre-operative anxiety. [ 54 , 55 ] With higher doses (0.75 mg/kg), melatonin was found to be more effective than midazolam for pre-operative anxiety without causing sedation and cognitive dysfunctions as midazolam did. [ 55 ] Patel et al (2015) found similar results with adults, whereas Caumo et al (2009) showed that melatonin was as effective as clonidine in reducing post-operative anxiety.…”
Section: Anxiety In Asdmentioning
confidence: 99%
“…Several pharmacological treatments to mitigate the production of free radicals have been studied (i.e. therapy with maternal glucocortico-steroids and allopurinol, erythropoietin and melatonin, but an ideal therapeutic strategy has not yet been found [9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…A dose range of melatonin premedication is used to provide sedation and analgesia without cognitive impairment and psychomotor skills, and without any increase in recovery time 512. Past studies have proven that melatonin is effective in the premedication of adults and children 131415. Anderson et al’s review7 which explored 24 clinical trials and 1749 participants suggested that melatonin decreases anxiety and pain, as compared to placebo.…”
Section: Introductionmentioning
confidence: 99%